2006
DOI: 10.1016/j.jvs.2006.07.051
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-derived endothelial cell growth factor gene therapy for limb ischemia

Abstract: This study demonstrated that PD-ECGF/TP gene transfer induced angiogenesis and decreased ischemia in a rabbit hindlimb model by promoting arteriogenesis, suggesting that targeting this gene may be a promising therapeutic strategy for peripheral vascular disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 31 publications
0
26
0
Order By: Relevance
“…In effect, the follow-up duration of most pre-clinical studies reporting benefits of gene therapy strategies on hindlimb ischemia has ranged from 1 week to 30 days. [22][23][24][25][26][27] Beneficial effects at longer follow-up times (up to 12 weeks) of AdVEGF 121 have been reported by Gowdak et al 28 in rats and rabbits with hindlimb ischemia. However, their results are not strictly comparable with ours because the gene was injected between 2 and 4 weeks before the induction of hindlimb ischemia.…”
Section: Discussionmentioning
confidence: 88%
“…In effect, the follow-up duration of most pre-clinical studies reporting benefits of gene therapy strategies on hindlimb ischemia has ranged from 1 week to 30 days. [22][23][24][25][26][27] Beneficial effects at longer follow-up times (up to 12 weeks) of AdVEGF 121 have been reported by Gowdak et al 28 in rats and rabbits with hindlimb ischemia. However, their results are not strictly comparable with ours because the gene was injected between 2 and 4 weeks before the induction of hindlimb ischemia.…”
Section: Discussionmentioning
confidence: 88%
“…12,13,33 In our previous study, we demonstrated the therapeutic effects of PD-ECGF/TP gene transfer on ischemia by promoting angiogenesis and inhibiting apoptosis (summary in Fig 5). [27][28][29] Sengupta et al 33 have reported that equimolar concentrations of PD-ECGF/TP induce a similar total monolayer recovery of wounded endothelium in vitro as well as vascular endothelial growth factor, strongly suggesting the chemotaxis functional effect of PD-ECGF/TP on endothelium. Therefore, as shown in Fig 5, we speculate that in addition to the suppressive effect of PD-ECGF/TP on VSMCs, PD-ECGF/TP itself, its enzymatic substrates, or PD-ECGF/TP-derived HO-1 expression may promote endothelial cell proliferation and protect endothelial cells from injury.…”
Section: Discussionmentioning
confidence: 94%
“…15,[27][28][29] We used gene transfection of human PD-ECGF/TP into rat VSMCs to study the mechanism of inhibitory effect of PD-ECGF/TP on VSMC, and found that inhibition of VSMC proliferation was correlated with the upregulation of p27 KIP1 and HO-1. 15 We also found that adventitial gene transfer of TP/PD-ECGF in a balloon injury rat carotid artery model markedly inhibited the intimal hyperplasia.…”
Section: Discussionmentioning
confidence: 99%
“…In some studies, intramuscular transfection was used to stimulate arteriogenesis [29,30,31]. However, although collateral artery growth can be enhanced, this method is not able to specifically target collateral arteries.…”
Section: Discussionmentioning
confidence: 99%